PENGARUH KINERJA PERBANKAN TERHADAP JUMLAH PENYALURAN KREDIT ATAU PEMBIAYAAN PADA BANK KONVENSIONAL DAN SYARIAH - Yunita Hasanah; Ida Busneti (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2016)
The goal this research to analyze comparing of factors that influence credit distribution at PT. Bank DKI and finance at PT. Bank Syariah Mandiri. The variable that influence credit distribution is: Third Party Funds, NonPerforming Loan/NonPerforming Finance and Capital Adequacy Ratio.This research used secondary data quertaly during the period 2008-2015 at the case study PT. Bank DKI and PT. Bank Syariah Mandiri from Finance Annual Reports of each Bank. The Methodology used is multiple regression analyze. This research shows is Third Party Funds and Capital Adequacy Ratio significantly and positive influence for the credit distribution and financing. NonPerforming Loan/NonPerforming Finance has a negative and significant effect for credit distribution and financing.